Чинники формування сільськогосподарської періодики на українських теренах - Анікіна, О. П. (НТУ "ХПІ", 2014)
Проаналізовано передісторію, причини виникнення сільськогосподарської періодики на теренах України. Неухильний розвиток сільського господарства, освіти, науки та процеси їх інституціалізації, ініціатива різних установ і організацій, окремих фахівців та вчених стали чинниками формування масиву видань. Поступово періодика стає дієвим засобом розвитку та популяризації, інформаційно-наукового супроводження галузі, науки освіти

Prehistory and reasons of agricultural periodicals appearance in Ukraine were analyzed. The steady development of agriculture, education, science and processes of their institutionalization, an initiative of different institutions and organizations, individual professionals and scientists has become the formation factors of mass publications. Gradually periodicals becomes an effective instrument for development and popularization of information and scientific support of the industry, science and education.
Keywords: перша третина ХХ ст.; сільське господарство; інформація; публіцистичні жанри; periodicals; Ukraine; agriculture; first third of XX century